Use multi-goal fuzzy programming to find the critical path - البدري, فاتن فاروق; علي, يوسف عادل (Journal of Economics and Administrative Sciences, 2019)
The exploitation of all available resources and benefiting from them is one of the most important problems facing the decision makers at the present time. In order to exploit these resources, it is necessary to organize the conflicting objectives, which is the main work in the project management, which enables the development of a plan that decision makers can use to shorten the total completion time and reduce the total cost of the project. Through the use of modern scientific techniques, and therefore the researcher using the critical path method using the technology of programming goals to find more efficient ways to make appropriate decisions where the researcher worked to solve the problems in the construction of the Department of sewage streams The results were within the level of ambition for the decision maker where the conflict between the objectives was resolved from reducing the total cost to the total time and the cost of evasion through Use linear programming objectives and the results were within the level of ambition of the decision-maker